Sodobni pogledi o nastanku revmatičnih bolezni - Vargazon, Bogomil; Kos-Golja, Mojca (Obzornik zdravstvene nege, 1977)
The article presents the etiology of the inflammatory, metabolic, degenerative and extraarticular rheumatism. As far as the inflammatory rheumatic diseases are concerned, it is only the etiology of the rheumatic fever that has been elucidated so far, while the causes of several chronic forms of these disorders still remain obscure. In addition to the hereditary disposition, the immuno-pathological processes are stated to determine the chronic nature of the disease, as well. Certain drugs can bring about systemic erythematodes. Heredity has been proved to play an important role in the development of primary gout, but its increasing incidence rate can also be ascribed to the better standard of living. While there is no evident external factor causing the primary arthrosis, the secondary arthroses occur as the consequence of injuries.